2002
DOI: 10.3310/hta6150
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the effectiveness and cost-effectiveness of metal-on-metal hip resurfacing arthroplasty for treatment of hip disease

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. NHS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 38 publications
1
40
0
Order By: Relevance
“…Prior studies have examined the cost-effectiveness of new technologies for use in THA. Vale et al [18] used clinical effectiveness data and cost data to estimate the costeffectiveness of metal-on-metal resurfacing for treating patients 65 years and older. The authors concluded metalon-metal resurfacing could be cost-effective versus conventional THA if revision rates were 20% lower.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have examined the cost-effectiveness of new technologies for use in THA. Vale et al [18] used clinical effectiveness data and cost data to estimate the costeffectiveness of metal-on-metal resurfacing for treating patients 65 years and older. The authors concluded metalon-metal resurfacing could be cost-effective versus conventional THA if revision rates were 20% lower.…”
Section: Discussionmentioning
confidence: 99%
“…The incremental cost per QALY gained for MOM compared with 'watchful waiting' diminishes until approximately 14.5 years after MOM, beyond which MOM dominates 'watchful waiting' [24]. MOM continued to dominate 'watchful waiting' even at 'watchful waiting' quality of life values of up to 0.963.…”
Section: Sensitivity Analysismentioning
confidence: 98%
“…the annual probability that following initial use of a treatment alternative a revision to a second procedure is necessary). A structured literature search was conducted to identify evidence relating to the clinical effectiveness of the three interventions for treatment of hip disease [24]. This included an electronic search of databases and websites.…”
Section: Event Probabilitiesmentioning
confidence: 99%
“…Vignettes for the exemplar of metal-on-metal hip resurfacing for osteoarthritis (OA) were developed from an uncontrolled study by McMinn et al [16] using the Charnley Hip Score, which includes items on pain and mobility [17]. Patients describe their condition by indicating which statement best describes themselves.…”
Section: Methodsmentioning
confidence: 99%